Multiple left ventricular thrombus following coronary artery bypass graft: An uncommonly documented case report - Hutomo, Malombassi Dharmawan Hadiwidjojo; Kurnianingsih, Novi; Muttaqin, Chaidar; Widito, Sasmojo (Heart Science Journal, 2026)
Background: Left Ventricular Thrombus (LVT) formation after Coronary Artery Bypass Grafting (CABG) is infrequent but may result in life-threatening embolic events. The occurrence of LVT following CABG is linked to impaired left ventricular function, regional wall motion abnormalities (RWMAs), hypercoagulability, and an increased inflammatory response subsequent to heart surgery. The interplay of these factors predisposes patients to thrombus development, particularly in those with a history of myocardial infarction, reduced left ventricle ejection fraction (LVEF), pre-existing endothelial injury, or hypercoagulable conditions. Case Presentations: A 65-year-old female with reduced LVEF, 36% by biplane, and RWMAs developed multiple LVT following CABG, as revealed by serial transthoracic echocardiography on postoperative day 6. There was no intracardiac thrombus confirmed preoperatively by transthoracic echocardiography and intraoperatively by transesophageal echocardiography. On follow-up, hypercoagulable risk factors was observed, and adenocarcinoma was diagnosed by bone survey and ultrasound-guided biopsy, suggestive of a metastatic process. A complete resolution of multiple LVTs was achieved after three months of administration of warfarin 2mg daily. Conclusions: This case underscores the importance of echocardiography surveillance among high-risk populations postoperatively. Prompt identification and early initiation of anticoagulants showed to be beneficial in hypercoagulable conditions in carcinoma patient as reported in this case.